2013
DOI: 10.1108/17468801311330329
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐demographic factors and network configuration among MENA entrepreneurs

Abstract: PurposeThe field of entrepreneurship has seen a dramatic increase in studies focusing on networks and relations. Research in this area has thus far focused on how the structure and quality of entrepreneurs' existing interpersonal ties shape information access and thereby influence entrepreneurial outcomes. The purpose of this paper is to extend the focus further by examining how the entrepreneur's socio‐demographic profile affects advisory network configuration in the Middle East and North Africa (MENA) contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 101 publications
1
10
0
1
Order By: Relevance
“…Perhaps the increasing age comes with more experience and knowhow in entrepreneurship as opposed to those of lower age group/s. The outcome validates the findings of Huang et al (2013) based on studies conducted in Middle East and North Africa. The aforementioned found that there is a strong interplay between age and entrepreneurs' ability to tap into advice-seeking networks.…”
Section: Discussionsupporting
confidence: 86%
“…Perhaps the increasing age comes with more experience and knowhow in entrepreneurship as opposed to those of lower age group/s. The outcome validates the findings of Huang et al (2013) based on studies conducted in Middle East and North Africa. The aforementioned found that there is a strong interplay between age and entrepreneurs' ability to tap into advice-seeking networks.…”
Section: Discussionsupporting
confidence: 86%
“…age, gender, work experience, education level) are also potentially important for explaining knowledge sharing behaviour. For example, previous research showed that male entrepreneurs more often discuss their work (share tacit knowledge) during interactions and have a larger business network than female entrepreneurs (Pangil and Nadurdin 2008;Klyver and Grant 2010;Zengyu Huang et al 2013). On the other hand, other studies did not find any relation between gender and knowledge sharing behaviour (Alhammad, Al Faori, and Abu Husan 2009).…”
Section: Demographics and Organizational Typementioning
confidence: 99%
“…On the other hand, other studies did not find any relation between gender and knowledge sharing behaviour (Alhammad, Al Faori, and Abu Husan 2009). In addition, findings of the study by Zengyu Huang et al (2013) suggest that people who are higher educated are more likely to use a professional network for advice, women are more likely to use personal networks than men and early stage entrepreneurs are more likely to use advice-seeking networks than later stage entrepreneurs.…”
Section: Demographics and Organizational Typementioning
confidence: 99%
“…Overall, the main purpose of this research is to analyze the location type choice for face-to-face interactions between users in business centers by testing the above set of hypotheses. To test the hypothesized relations, we control for differences in personal and work-related characteristics (e.g., age, gender, education level, organization type), which can also be related to interaction behavior (e.g., Greve & Salaff, 2003; Klyver & Grant, 2010; Zengyu Huang, Nandialath, Alsayaghi, & Karadeniz, 2013).…”
Section: Office Type Workpace Use and Social Interactionmentioning
confidence: 99%